Catalytic amidation of unactivated ester derivatives mediated by trifluoroethanol1. Issue 46 (11th June 2015) - Caldwell, Nicola; Jamieson, Craig; Simpson, Iain; Watson, Allan J. B.
<x xml:space="preserve">Abstract</x> A practical, catalytic protocol for amidation of unactivated esters has been developed using cheap and readily available reagents.